Ilmu Hukum Sebagai Keilmuan Perspektif Paradigma Holistik - Arief Budiono; Wafda Vivid Izziyana (Jurnal Hukum Novelty, 2018)
The thought of law science today is getting stagnant and being doubtful because it tends to be mainstream positivistic. Positivism paradigm is a rigid paradigm, autonomous, and the law becomes merely a law that reduces the law itself to be simple, linear, mechanistic and deterministic then it raises the condition that positive justice is a procedural justice and not an essential justice. The positivist concept produces an incomplete legal study and then it is being dry, stiff and unable to explain the reality. Such of this condition causes an anxiety then the law science requires a shift paradigm so that there is no gap between Das Sein and Das Sollen. Therefore, the holistic paradigm has become the choice for legal science to be genuine science and signifies that the real science of law is not static but dynamic. This paradigm is an effort to formulate the science of law as a unity of science which is full of values and philosophy to reveal truth and justice to the level of meaning.